Development of Learning Media Using Genially to Increase Student Learning Interest at Smk Muhammadiyah 2 Kuningan in Basic Graphic Design Subjects - Irpan, Muhammad; Lutfi, Ahmad Fajri (Syntax Corporation Indonesia, 2024)
Muhammad Irpan (201223025). Development of Learning Media Using Genially to Increase Student Interest in Learning at SMK Muhammadiyah 2 Kuningan in Basic Graphic Design Subjects. The background to this thesis is that students' interest in learning at SMK Muhammadiyah 2 Kuningan in the Basic Graphic Design subject is still relatively low. This is caused by learning methods that are less interesting and interactive. Genially is an online platform that allows the creation of interesting and interactive learning media. The aim of this thesis is to develop learning media using Genially to increase students' interest in learning in the Basic Graphic Design subject. The main problem in this research is